The Antesedent Of Job Insecurity And Work Stress On Job Satisfaction In Tourism Industry - I Gusti Putu Agung Widya Goca; Ni Putu Putri Ayu Wijayanthi (Bali International University, 2021)
The advancement of the travel industry in Bali, has gotten open consideration as a vocation that guarantees salary. To examine the impact of work stress hands on job insecurity of drivers of the Blue Bird Bali organization and to break down the mediating role of work stress on the impact of job insecurity hands on work satisfaction of drivers the Blue Bird Bali organization. This study uses 67 driver respondents as a samples, from the amount 200 be identified. Data collection by online questionnaires. This research tested by quantitative methods with SEM-PLS analysis. The results of hypothesis testing indicate that 1 of 4 hypotheses were rejected and accepted. Relationship of job insecurity to work stress, job insecurity in job satisfaction affect positively, work stress for job satisfaction affect negatively, and work stress mediate on job insecurity to job satisfaction. This exploration is identified with the assurance of tests utilizing arbitrary inspecting system which chooses one work move, then the following examination can apply another example assurance procedure. These research model enriches the concept of human behavior in job satisfaction. This results indicate that human in their behavior on job insecurity, and work stress. This paper contributes scholars by examining the job insecurity with work stress and how it relates to job satisfaction.